Exploring the Role of Family Gender Equality in Shaping Fertility Intentions in Indonesia - Muthia, Azka; Setyonaluri, Diahhadi (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: This study aims to investigate how a husband's participation in housework impacts women's fertility intentions. While previous studies have explored individual determinants, the role of a husband's participation in housework remains under-examined in the context of Indonesia. Objective: The primary aim of this study is to empirically analyze the relationship between a husband's participation in housework and fertility intentions in Indonesia. Method: The study uses data from Susenas 2022 and applies ordinal logit analysis. The hypothesis is that a higher level of a husband's participation in housework positively correlates with greater fertility intentions among women. Results: The analysis reveals that women whose husbands participate in housework are more likely to have higher fertility intentions compared to those whose husbands do not participate. Other significant factors influencing fertility intentions include parity, education level, employment status, and geographic region. Conclusion: The study concludes that a husband's participation in housework is important because it influences women's fertility intentions in Indonesia. Promoting gender equality in domestic responsibilities may encourage higher fertility intentions. These findings are important for policymakers aiming to enhance gender equality and address fertility issues in Indonesia.